Study on Strength Properties of Concrete with Ceramic Waste Aggregate and Silica Fume Admixture - G, Suresh; S, Harishankar (International Journal of Engineering and Technology, 2018)
The ceramic waste is used as a coarse aggregate replacement in concrete is a two way beneficial process that involves minimization of resources for construction and processing of hazardous industrial wastes that cannot be recycled. The ceramic waste obtained from waste dismantled building were used as coarse aggregate 10%, 20%, 30%, 40% and 50% replacement.Â To improve the mechanical properties silica fume is added as admixture in the concrete. The optimum percentage replacement was obtained considering the strength as well as the objective of using ceramic waste aggregate. The compressive strength of concrete cubes were tested . The compressive strength of aggregate replaced concrete has been compared to that of conventional concrete and the results are evaluated.Â